The Poetry of Meng Haoran - Kroll, Paul W. (Library of Chinese Humanities, 2021)
Meng Haoran (689-740) was one of the most important poets of the "High Tang" period, the greatest age of Chinese poetry. In his own time he was famous for his poetry as well as for his distinctive personality. This is the first complete translation into any language of all his extant poetry. Includes original Chinese texts and English translation on facing pages.